Reinforcement strategies for 3D‐concrete‐printing. Issue 4 (8th October 2020) - Kloft, Harald; Empelmann, Martin; Hack, Norman; Herrmann, Eric; Lowke, Dirk
Abstract: The ingenious bridge, roof, and shell structures of the last century were designed from the understanding of the congenial interaction of the two materials concrete and steel. Nowadays, reinforced concrete is the most widely used material in construction. The use of system formwork and easy‐to‐install reinforcement support structures that are optimized in terms of labor costs, but often have inefficient use of material. In this context, Stefan Polónyi has repeatedly criticized the engineers' lost understanding of the interaction of concrete and reinforcement. With Additive Manufacturing, an innovative digital manufacturing technology is now available that allows new freedom in concrete design with a resource‐efficient use of materials at the same time. With regard to practical application, the integration of reinforcement represents a central challenge in 3D‐concrete‐printing. The authors see here the future chance of a force‐flow controlled reinforcement layout. The paper shows new strategies for the combined Additive Manufacturing of concrete and reinforcement and presents first 3D‐printed reinforced concrete elements.